Valoração econômica : um estudo de caso sobre o papel dos cupins de montículo, beneficio-custo para o produtor pecuário - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
The scientometric contributes to the understanding of the state of the art in a scientific field. Through it is possible to identify which areas need to be investigated and realize new areas emerging. Environmental economics is a new interdisciplinary field within science and seeks a solution to environmental damage caused by human impacts incorporating economic principles to biological knowledge. This study aims to describe and analyze trends in scientific production in economic valuation of ecosystem services, analyze temporal trends of these publications, conduct a survey of the scientific literature on how, where and what services are being valued and who are performing the work and to survey the scientific production in economic valuation related to ecosystem services performed by termites. For this was made a search for articles published between 1991 and 2015, the Thomson-ISI database in the main collection of Web of Science to find the time trend and selected articles in the relevant time interval for the other objectives. For the temporal trend analysis it was found that period there was an increase of publications (r = 0.85; p <0.01), most of which were theoretical studies (83%). In the last four years, the found articles 2062, it was revealed the predominance of valuation "landscapes" and ecosystem services of the category "cultural". Of the articles about invertebrates the most valued service was the regulation, especially for pollination. Already six articles about termites not value their services and only one associated with termite ecosystem services. The theme of environmental economy has grown, but still there are services globally important organisms and landscapes that are not being emphasized by the studies. On the other hand, there are expectations that with the increase in research, regions and groups of organisms still understudied be further explored in order to ensure better conservation of biodiversity.
Keywords: Análise da produção científica; Economia ambiental; Cupins; Cienciometria; Analysis of scientific production; Environmental economics; Termites; Scientometric; CIENCIAS BIOLOGICAS